Новые виды наездников-ихневмонид (Hymenoptera, Ichneumonidae) из Средней Азии и с Кавказа - Каспарян, Д.Р. (Вестник зоологии, 1985)
Liotryphon pronotalis sp. n. (Pimplinae) pe- culiar by completely black pronotum, tegulae and fore coxae. Type-locality: 25 km ESE of Dehkanabad, Uzbek SSR. Rhorus caucasicus sp. n. (Ctenopelmatinae) closely related to Rh. mesoxanthus Gra v., differs by black abdomen with whitish-yellow band on hind margin of 2 and 3 tergites. Type-locality: Zakatalski zapovednik, 21 km NW of Zakataly, Azerbaijan SSR. A key to three Palearctic species of Drepanoctonus is given; two of them are for the first time recorded from the USSR territory: D. bicolor Kusigemati (Primorski krai, Kunashir island) and D. tricoloratus (Šedivý) (Eastern Ukraine, Georgia, Chita region).